Local variations of bulk hydrogen and chlorine‐equivalent neutron absorption content measured at the contact between the Sheepbed and Gillespie Lake units in Yellowknife Bay, Gale Crater, using the DAN instrument onboard Curiosity. Issue 6 (13th June 2014) - Litvak, M. L.; Mitrofanov, I. G.; Sanin, A. B.; Lisov, D.; Behar, A.; Boynton, W. V.; Deflores, L.; Fedosov, F.; Golovin, D.; Hardgrove, C.; Harshman, K.; Jun, I.; et al.
Abstract: Data gathered with the Dynamic Albedo of Neutron (DAN) instrument onboard rover Curiosity were analyzed for variations in subsurface neutron flux and tested for possible correlation with local geological context. A special DAN observation campaign was executed, in which 18 adjacent DAN active measurements were acquired every 0.75–1.0 m to search for the variations of subsurface hydrogen content along a 15 m traverse across geologic contacts between the Sheepbed and Gillespie Lake members of the Yellowknife Bay formation. It was found that several subunits in Sheepbed and Gillespie Lake could be characterized with different depth distributions of water‐equivalent hydrogen (WEH) and different chlorine‐equivalent abundance responsible for the distribution of neutron absorption elements. The variations of the average WEH at the top 60 cm of the subsurface are estimated at up to 2–3%. Chlorine‐equivalent neutron absorption abundances ranged within 0.8–1.5%. The largest difference in WEH and chlorine‐equivalent neutron absorption distribution is found between Sheepbed and Gillespie Lake. Key Points: DAN special campaign in Yellowknife Bay DAN local measurements of water and chlorine abundance Correlation of DAN measurements and geological context